Organisasi Non-Profit Sebagai Media Tindak Pidana Pencucian Uang - Sirait, Ningrum Natasya; Rangkuti, Liza Hafidzah Yusuf (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
Non-Profit Organisations (NPOs) as known as Foundation received attention when there was suspicion of money laundering. Several cases that has become the highlight is the Aksi Cepat Tanggap Foundation (ACT) and Yayasan Keadilan Untuk Semua Foundation (YKUS). In its development, the Foundation has been used as a medium for money laundering due to weak regulations on the organization of the Foundation. This study aims to find out how the law regulates Foundation, maps risk factors and preventive measures against Foundation as a medium for money laundering crimes. The research is normative using statutory and conceptual approaches. The results showed that Foundation are regulated through laws and government regulations, there are four risk factors for running Foundation as a medium for money laundering, namely anonymous donations/mysterious donors, overvaluation of donation assets, misuse of funds, and other unusual transactions. Likewise, the importance of applying proper due diligence procedures as an effort to prevent money laundering in accepting foundation donations. The conclusion is that money laundering threatens the integrity and stability of the system and financial institutions, including Foundation. Regulations for Foundation in Indonesia are still limited, not yet comprehensive and highly vulnerable to money laundering, so further research is needed to compare laws and regulations in other countries related Foundation.